Optimalisasi Penggunaan Google Clasroom dalam Bimbingan Skripsi Mahasiswa - Latifah, Eny; Wijayanti, Iin; Yusuf, Yusuf (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital era and the development of information technology have brought significant changes in the world of education, encouraging the adaptation of learning and guidance methods in a more flexible and efficient direction. One of the relevant and widely used platforms in the context of distance learning is Google Classroom. This PKM implementation method uses an interactive training and mentoring approach involving supervisors and students. Google Classroom optimization changes the paradigm of thesis guidance to a more structured, transparent, and adaptive process to the needs of the digital era. By making the most of its features, the quality and efficiency of the mentoring process can be significantly improved. In addition, the use of Google Classroom allows documentation of the guidance process to be carried out systematically, making it easier to monitor thesis progress and communication between lecturers and students. However, there are a number of challenges, especially related to limited access to technology, digital literacy, and limited direct interaction. Effective solutions include digital literacy training, the provision of additional communication channels, the use of features in a structured manner, and increased technology support so that the mentoring process